2016
DOI: 10.3168/jds.2015-10806
|View full text |Cite
|
Sign up to set email alerts
|

Repeated intrauterine infusions of lipopolysaccharide alter gene expression and lifespan of the bovine corpus luteum

Abstract: Inflammation of the uterus is associated with disturbed ovarian function and reduced reproductive performance in dairy cows. To investigate the influence of endometritis on the bovine corpus luteum, 8 heifers received intrauterine infusions with either phosphate-buffered saline (PBS; 9mL) or Escherichia coli lipopolysaccharide (LPS; 3µg/kg of body weight diluted in 9mL of PBS) at 6-h intervals from 12h before and until 9d after ovulation during 2 cycles in a random order (ovulation=d 1). An untreated cycle was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 62 publications
1
14
1
Order By: Relevance
“…Other papers, including some by this group (Cerri et al, 2012;Davoodi et al, 2016), have also included genes that had lower differential magnitude. Compared with recent studies that used intrauterine LPS infusion (Lüttgenau et al, 2016) or cows diagnosed with subclinical and clinical endometritis (Salilew-Wondim et al, 2016), the present study observed significantly smaller fold change in the endometrium gene expression. Even in the papers describing uterine disease, genes with lower fold change are also presented.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Other papers, including some by this group (Cerri et al, 2012;Davoodi et al, 2016), have also included genes that had lower differential magnitude. Compared with recent studies that used intrauterine LPS infusion (Lüttgenau et al, 2016) or cows diagnosed with subclinical and clinical endometritis (Salilew-Wondim et al, 2016), the present study observed significantly smaller fold change in the endometrium gene expression. Even in the papers describing uterine disease, genes with lower fold change are also presented.…”
Section: Discussioncontrasting
confidence: 91%
“…Tumor necrosis factor-α induces premature release of PGF 2α from the endometrium (Miyamoto et al, 2000), resulting in luteolysis and a gradual decrease of progesterone levels that are incompatible with gestation (Giri et al, 1990;Skarzynski et al, 2000;Hansen et al, 2004). Recently, Lüttgenau et al (2016) reported that repeated intrauterine infusions of LPS at the onset of the estrous cycle promoted premature luteolysis and altered endometrial and corpus luteum (CL) gene expression. Therefore, the negative effect of infection on reproductive tract functionality is probably due to a direct effect of endotoxin added to indirect effects of inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive and inflammatory response to acute LPS exposure has been well chronicled (Giri et al, 1990;Lüttgenau et al, 2016). However, natural infection likely causes a more persistent and dynamic LPS exposure, reflective of bacterial overgrowth and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Herath et al (2009) also showed in vivo and in vitro evidence for production of PGE compared with PGF 2α in cows with E. coli infection. Lüttgenau et al (2016), however, found the opposite effect in heifers. Intrauterine infusion of LPS decreased progesterone concentrations and reduced the lifespan of the corpus luteum in the cycle when LPS was infused, but also in the subsequent cycle.…”
Section: Effects Of Uterine Disease On Ovarian Structures and Their Pmentioning
confidence: 89%